Surfactants from the group of fatty acids polyethylenated esters. Part II. Basic viscometric values and solubility parameter in relation to hydrophilic-lipophilic balance of the products of oxyethylenation of rape oil fatty acids methyl esters - Zgoda, M. M.; Woskowicz, M.; Nachajski, M.; Kołodziejczyk, M. K.; Lukosek, M.; Jerzykiewicz, W. (Polimery, 2022)
Aqueous solutions of homologous series of "Rofam" type surfactants (ZPC) based on rape oil fatty acids methyl esters, differing in oxyethylene segments content (nTE), were the subjects of investigations. Content of oxyethylene segments nTE, determined by 1H NMR, allowed to verify ZPC molecular weight and to calculate structural hydrophilic-lipophilic balance (HLB, by Davis or Griffin methods) as well as required solubility level of the balance (HLBR) (Table 1). The following values were determined on the basis of viscometric measurements: limiting viscosity number [h], viscometric average molecular weight (Mh), specific volume (W) and hydrodynamic radius of micelle (Robs) (Table 2 and 3). Viscometric measurements let also calculate average number of water molecules hydrating the micelle built of "Rofam" homologous structures. Determination of critical micellar concentration (cmc) was the base for calculation of thermodynamic potential of micelle formation (***) and micellar level of hydrophilic-lipophilic balance (HLBcmc) (Table 4, Fig. 1-3). The value of surfactant's lipophilic core upthrust over the phase boundary (Am, Fig. 4) let analyze the effect of oxyethylene segments' content in "Rofam" molecule structure on its potential solubilization properties. The results of investigations and the values calculated on this basis make clearer the mechanism of solubilization of lipophilic drugs what determines the pharmaceutical and biological availability of micellar adducts from the model forms of drugs.